Implementation of East Ogan Komering Ulu Regent Regulation Number 17 of 2015 Regarding Technical Guidelines for Implementing Micro and Small Business Permits - Andriani, Nety; Widodo, Slamet; Alfatih, Andy (Open Access Indonesia Journal of Social Sciences, 2018)
ABSTRACT The purpose of this research is to find out how the implementation of East Ogan Komering Ulu (OKU) Regency Regulation Number 17 of 2015 regarding Technical Guidelines for Micro and Small Business Permits in three sub-districts in East OKU Regency and also to find out the factors that support and hinder the implementation of policies. The policy implementation is analyzed using three variables; the level of compliance, well-functioning routines, and the absence of problems, and the desired performance and impact of the policies implemented. The results showed that East OKU Regency Regulation No. 17 of 2015 concerning Technical Guidelines for Micro and Small Business Permits in three districts in East OKU Regency has not been implemented optimally. This is indicated by some costs that entrepreneurs must pay when they want to get a license, micro and small licensing processes that have been done in real time, reports on the implementation of micro and small licenses that have not been done by the district, and supervision from the Office of Cooperatives and Small and Medium Enterprises is not fully done. In line with that, the researchers found the factors that supported the successful implementation of the policy were efforts to take a license application from employers and the achievement of delivery time. While the factors that hinder the successful implementation of this policy are the unavailability of the budget, lack of infrastructure and working equipment, uneven network and internet connections, and lack of coordination. Therefore, improvements need to be made by meeting the resources needed, and also to maximize training and supervision of the implementation of micro and small licenses by the Office of Cooperatives and Small and Medium Enterprises.